2007
DOI: 10.1111/j.1442-2042.2007.01764.x
|View full text |Cite
|
Sign up to set email alerts
|

Is a complete urological evaluation necessary in all newborns with asymptomatic renal ectopia?

Abstract: Aim:To evaluate if a complete urological screening is justified by potential urological anomalies in newborns or infants with asymptomatic renal ectopia (RE). Methods: The database records of 60 consecutive neonatal cases of RE diagnosed at the authors' hospital from 1990 to 2004 were retrospectively reviewed. Results: At diagnosis, mean patient age was 1.6 months. In 58 of 60 patients, the suspected diagnosis of RE was made during prenatal or postnatal screening ultrasonography, including two newborns with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 12 publications
2
33
0
8
Order By: Relevance
“…In a review of 32,221 newborn screening ultrasounds, renal ectopia was identified in 60 (0.2%), 40% of which were crossed [3]. Of note, 40% of the patients with renal ectopia had additional urological abnormalities including vesicoureteral reflux (25%), and ureteropelvic and ureterovesical junction obstruction.…”
Section: Discussionmentioning
confidence: 96%
“…In a review of 32,221 newborn screening ultrasounds, renal ectopia was identified in 60 (0.2%), 40% of which were crossed [3]. Of note, 40% of the patients with renal ectopia had additional urological abnormalities including vesicoureteral reflux (25%), and ureteropelvic and ureterovesical junction obstruction.…”
Section: Discussionmentioning
confidence: 96%
“…Associated urological anomalies have been observed in *40% of patients with CSFK [15]. In particular, VUR was more frequently associated with CSFK [16] (15% of cases), followed by pyeloureteral junction obstruction (PUJO) (12%), ureterovesical junction obstruction (2%), and other urological anomalies in 9% of children with CSFK [5,7,16,17].…”
Section: Physiopathologymentioning
confidence: 98%
“…99m Tc-DMSA scan and contrast-enhanced multidetector CT were recommended to evaluate renal ectopia. 1 Left-to-right ectopia is more common than right-to-left. 2,3 In addition, approximately 90% of crossed ectopic kidney are fused to the ipsilateral kidney.…”
Section: Figurementioning
confidence: 98%
“…In some cases, it may be associated with recurrent urinary tract infections, nephrolithiasis, vesicoureteral reflux, ureteropelvic junction obstruction, hydronephrosis, and multicystic renal dysplasia. 1,5 Although ultrasound is the first imaging study to start the diagnostic approach, a single kidney usually identifies in renal fossa with increased size and dilated renal pelvis, which suggest unilateral renal agenesis, and further imaging studies are required. 6,7 99m Tc-DMSA scan can reveal the location of functioning renal tissue with a high degree of sensitivity, 3,8 and additional SPECT imaging may be helpful to find any morphologic anomalies and cortical defects.…”
Section: Figurementioning
confidence: 99%